The Factors Influence on the Smokers in the Low Income Group : Case Study in Malaysia - Abdelrahman, Osman Elsheikh (2009)
Several variable were used to characterize the relationship between social factors such are gender, age, education level, income level, health effect, years of smoking increase cigarette price and smoking rate conducted in this study lower income groups smoking in Malaysia by questionnaire survey. These variables were analyzed by reliability test, ANOVA tables, correlation and regressions. The result found that the reliability test found that all variable significant except the increase cigarette price. The ANOVA tables correlation and regression analysis also found that all variables are significantly have relationships with each other found. Except increase of cigarette price which is not significantly with these variables. Also all study variable were found in a good agreement with the study hypotheses assumed in the present work.